Transkarunkulárna mediálna orbitotómia - Almasi, M; Osifová, A; Hornák, A; Andrasovská, M; Dzunková, N (Ceska a slovenska oftalmologie, 2011)
Transcaruncular medial orbitotomy is a tissue preserving, time sparing and cosmetically acceptable approach, which is appropriate for treatment of various pathological conditions, as fractures of the medial orbital wall, inflammatory expansions and tumours of adjacent part of the orbit, but also the orbital endokrinopathy and correction of the medial palpebral ligament. Surgical technique and authors' first experience with this approach in female with orbital haemangioma is presented.
Keywords: oftalmologické chirurgické výkony; Humans; orbita; lidé středního věku; Middle Aged; ženské pohlaví; nádory orbity; Orbital Neoplasms; lidé; Orbit; Ophthalmologic Surgical Procedures; Female